Confusing constructions: Exploring the meaning of health with children in "obesity" treatment. Issue 3 (2nd September 2017) - Ward, Pamela; Beausoleil, Natalie; Heath, Olga
ABSTRACT: Fat studies scholars challenge the notion of the "obesity epidemic, " explicating how "obesity" discourse serves to shape our views of health and the body. It is argued that childhood "obesity, " in particular, has been constructed as a modern day scourge that threatens the future health of populations. The authors provide an examination of the embodied experiences of children enrolled in an "obesity" treatment program in a Canadian hospital. Utilizing a feminist poststructural framework, they provide narratives illustrating how these children construct their meanings of health and how "obesity" discourse restricts fat children's opportunity to identify as healthy.